Reduction in the absorption of copper and manganese in solution by wheat cultivars inoculated with a Pseudomonas sp - Voss, Márcio; Wayne Stephen Phillip Thomas, Robert (Pesquisa Agropecuaria Brasileira, 1998)
The capacity of several microorganisms to adsorb metals from solution was demonstrated, but the implication of these phenomenon on the wheat nutrition hasn’t been evaluated. The present study had this objective, observing the absorption of copper and manganese ions by wheat (Triticum aestivum L.) cultivars Anahuac and BR 35 in the presence of a Pseudomonas isolated from wheat rizosphere. The concentration of these metals in the tissue of wheat was determinated by nitroperchloric and spectrophotometry of atomic absorption, in the above-ground parts of 18-day old wheat plants, after 2 days in contact with an exclusive solution of CuCl2 or MnCl2. The inoculation with Pseudomonas sp. reduced the concentrations of Cu2+ and Mn2+ in the tissue of seedlings by 70% and 35%, respectively, in the two cultivars. Such effect was attributed to the competition of the bacteria with the plants for these metals, through sorption process, specially by the adsorption to the bacterial wall.